Proposed new interior design scheme for junk youth community centre at No. 1 & No. 2, Jalan Telawi 3, Bandar Baru Bangsar, 59100 Bangsar, Kuala Lumpur / Noor 'Atiqah Saleh - Saleh, Noor 'Atiqah (Faculty of Architecture, Planning and Surveying, 2010)
Basically, the final project of interior design for final semester students is the representation of students' understanding towards the process and important aspects of interior designing that has been studied and analyzed from the only the basic knowledge of managing the project to the presentation stage of final design proposal. The project in this report is a new designed scheme project on a community centre of Junk Magazine for Freeform Sdn. Bhd. This project is proposed to be at No. 1 and No. 2 of Jalan Telawi 3, Bandar Baru Bangsar, Kuala Lumpur. Nowadays, in Malaysia, youth has started to involve into local acts on art, entertainment, music and fashion. Therefore, this proposed project are intentionally to become the platform for them local acts or even internationals to meet to their audiences and bring them to a higher level apart from appreciating their talent and skills. This community centre also provide area to commercialize, exhibit and demonstrate all sort of arts to serve those local acts’ purpose better. The aim of this interior design project is to provide a suitable space with facilities & activities specified for youth community that can satisfy their entertainment & art passion in a better way as well as to expose and share everything in common to the people among the community and bring knowledge for other people in the country or all over the world about local scenes of Malaysia and the independent acts’ inner talent. With all the specification and design approaches, this centre will be diverse from other comunity centre in Malaysia. Design concept and implementation will act as profoundest study. All the data and details that been collected from research and observation conducted, was use as a parameter in the design process.